Cottonseed Oilcake Extract Mediated Green Synthesis of Silver Nanoparticles and Its Antibacterial and Cytotoxic Activity. (7th September 2016) - Govarthanan, Muthusamy; Cho, Min; Park, Jung-Hee; Jang, Jum-Suk; Yi, Young-Joo; Kamala-Kannan, Seralathan; Oh, Byung-Taek
Abstract : Agroindustrial byproduct mediated green synthesis of silver nanoparticles was carried out using cottonseed oilcake (CSOC) extract. The aqueous silver nitrate formed stable silver nanoparticles with CSOC extract as a reducing agent for Ag + to Ag 0 . The synthesized nanoparticles were characterized using energy dispersive X-ray spectroscopy (EDS), transmission electron microscopy (TEM), Fourier transform infrared (FTIR) spectroscopy, and X-ray diffraction (XRD) techniques. The synthesized silver nanoparticles (AgNPs) (4 mM) significantly inhibited the growth of phytopathogens, Pseudomonas syringae pv. actinidiae and Ralstonia solanacearum . Further, cytotoxicity of AgNPs was evaluated using rat splenocyte cells. The splenocyte viability was decreased according to the increasing concentration of AgNPs and 90% of cell death was observed at 100 μ g/mL.